Modelling hepatotoxicity and antiretroviral therapeutic effect in HIV/HBV coinfection - Luboobi, Livingstone S.; Nampala, Hasifa; Mugisha, Joseph Y.T.; Obua, Celestino; Sabuka, Matylda Jablonska (Elsevier, 2018)
Enzyme alanine aminotransferase (ALT) elevation which reflects hepatocellular injury is a current challenge in people infected with human immunodeficiency virus (HIV) on antiretroviral therapy (ART). One of the factors that enhance the risk of hepatotoxicity is underlying diseases such as hepatitis caused by hepatitis B virus (HBV). HIV/HBV coinfected patients stand a greater risk of hepatotoxicity because all ART are toxic and liver cells (hepatocytes) that are responsible for metabolising the toxic ART, support all stages of HIV and HBV viral production. Mathematical models coupled with numerical simulations are used in this study with the aim of investigating the optimal combination of ART in HIV/HBV coinfection. Emtricitabine, tenofovir and efavirenz is the optimal combination that maximises the therapeutic effect of therapy and minimises the toxic response to medication in HIV/HBV coinfection.
Keywords: Modelling hepatotoxicity; Antiretroviral therapeutic effect; HIV/HBV coinfection